PREMATURE MORTALITY (AGES 30-60) AND NON-COMMUNICABLE DISEASES: THE ROLE OF LIFESTYLE IN NIGERIA - Adebayo, Emeka Josephine (Research Journal of Health, Medicine and Nursing, 2024)
This study investigates the intricate relationship between lifestyle factors and the prevalence of non-communicable diseases (NCDs) in Nigeria. Rapid urbanization and globalization have significantly influenced dietary patterns, physical activity levels, and substance use, contributing to the rising burden of diseases such as hypertension, diabetes, cardiovascular diseases, and cancers. This research adopts a mixed-methods approach, integrating quantitative data from surveys and health records with qualitative insights from interviews and focus groups. This comprehensive approach provide a nuanced understanding of the socioeconomic determinants and regional disparities impacting NCD prevalence in Nigeria. The findings reveal a pervasive adoption of unhealthy lifestyles characterized by diets high in salt, sugar, and saturated fats, coupled with sedentary behaviors and low physical activity levels. Tobacco use and harmful alcohol consumption further exacerbate these risk factors, showing significant variations between northern and southern regions. Theoretical insights drawn from the social determinants of health theory, the Health Belief Model, and Health Promotion and Behavioral Change approaches guide the analysis. These frameworks underscore the influence of socio economic conditions, cultural norms, and health behaviors on individual health outcomes related to NCDs. Addressing these challenges requires a collaborative, multisectoral approach involving government agencies, healthcare providers, educational institutions, community organizations, and the private sector. Policy recommendations include implementing targeted health promotion campaigns, improving access to nutritious foods, and integrating comprehensive NCD prevention and management strategies into primary healthcare services. This study underscores the urgent need for evidence-based interventions tailored to local contexts to combat the escalating burden of NCDs in Nigeria. By promoting environments conducive to healthy lifestyles and enacting effective policies, Nigeria can enhance population health outcomes and mitigate the prevalence of lifestyle-related risk factors nationwide